PROFESIONALISME MENGEMBAN FUNGSI UTAMA KEPOLISIAN DALAM PENEGAKAN HUKUM DI POLDA JAWA TENGAH - Erlyn Indarti (Masalah-Masalah Hukum, 2014)
Police, in whatever meanings, is a profession. It is said so because to become - or in other words to be referred to as- police, one is required to go through education and training, acquire theoretical as well as technical experties, belong to a formal organization, live one's life based on a set of code of conduct and disciplinary rule, and attain a strong altruistic commitment to public service, as consently  drawn and agreed by the whole members of the community of such profession. In this regard, public demand of the enhancement of professionalism of police principle functional role, i.e. investigation, intelligence, traffic management, police vigilance and alacrity, and community building, is eminent